Aggregate Investment and Investor Sentiment - Arif, Salman; Lee, Charles M. C. (Review of Financial Studies, 2014)
Using bottom-up information from corporate financial statements, we examine the relation between aggregate investment, future equity returns, and investor sentiment. Consistent with the business cycle literature, corporate investments peak during periods of positive sentiment, yet these periods are followed by lower equity returns. This pattern exists in most developed countries and survives controls for discount rates, equity flows, valuation multiples, operating accruals, and other investor sentiment measures. Higher aggregate investments also precede greater earnings disappointments, lower short-window earnings announcement returns, and lower macroeconomic growth. We conclude aggregate corporate investment is an alternative, and possibly sharper, measure of market-wide investor sentiment.